Study of stator addition to a Rim-driven propeller using computational fluid dynamics - Low, Brandon Jian Jun (Nanyang Technological University, 2020)
Rim-driven propellers (RDP) is relatively new in today’s propulsion technology. It is a new concept of electronic propulsion, which integrates the motor and propeller directly. Fewer researches have been conducted in terms of efficiency of the RDP as compared to conventional propellers. In this study, it hopes in incorporating similar concepts from hub-propellers into an RDP, applying changes in hopes of obtaining better efficiency. To do so, computational fluid dynamic (CFD) is applied to simulate the fluid flow of a SEAThrust T160 Rim-driven propeller. To improve efficiency the study of the addition of stator blades were conducted. Two variables were used in this study, namely an increased number of blades and an increased distance between propeller and stator.